The Relationship Between Work Conflict and Nurses Work Life Balance In the Hospital - Tanti, Nurin Farissa Dwi Suparman; Suratmi, Suratmi; Qowi, Nurul Hikmatul; Jaenudin, Muhammad Fadoli (STIKES Adi Husada, 2025)
Nurses work conflict due to lack of balance between work and personal life in health services. Nurses, as the largest health workforce, should have a high work-life balance so they can provide quality service to patients. The aim of this research is to analyze the relationship between work conflict and nurses' work life balance. This research design uses a cross-sectional approach. The population was 107 nurses and selected using cluster random sampling so that there were 81 nurses. Research data was taken using a questionnaire instrument. Research shows that almost all (97.5%) nurses experience high work conflict, and almost all (67.9%) experience low work-life balance. Based on the results of the analysis using the Spearman Rho test, the value of p = 0.000 (p <0.05) and value = -0.618, meaning that H1 is accepted so that there is a relationship between work conflict and work life balance among nurses. Organizational support and the role of superiors play an important role in reducing work conflict and increasing work life balance with minimal conflict occurring in the workplace.